THE ROLE OF EDUCATIONAL STANDARDS IN IMPROVING THE MANAGEMENT SKILLS OF PRESCHOOL EDUCATION ORGANIZATION DIRECTORS - Mominov Durbek Nomonovich (Web of Journals Publishing, 2025)
This article discusses the role of educational standards in improving the managerial skills of directors of preschool educational organizations.
Keywords: Preschool education, managerial skills, professional competence, national education, state educational standards, personnel management, professional development system, social cooperation.